Dental arch symmetry analysis in orthodontic treatment - Kurniawan, Irsan; Soeria Soemantri, Eky Setiawan; Evangelina, Ida Ayu (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The aims of this study were to introduce fixed symmetrograph as a device to analyze arch symmetry and to compare the result of arch symmetry measurements using such appliance with commonly used symmetrograph in Faculty of Dentistry Padjadjaran Universitas (Orthocross). Twenty based study models used in this study. The method used in this study was by comparing the result of measurement using orthocross with the result of measurements using fixed symmetrograph. The result of this study revealed there was no significant difference between measurement using orthocross with measurement using fixed symmetrograph (P>0,05). Based on the result of this study, it is recommended to use this fixed symmetrograph, because there were several advantages using this device, for example, symmetrographâs midlines superimpose exactly with study modelâs midlines with the aid of two vertical pins. Even more, the study model can be fixated using two fixators so that the study model and fixed symmetrograph were not moving during measurement.